Construction properties of equity fund of funds: a preliminary note from the Greek market. (8th June 2011) - Samitas, Aristeidis; Stavridou, Eleni; Asimakopoulos, Ioannis
This study examines return and risk properties arising from the construction of fund of funds (FoF) portfolios utilising actively managed Greek equity mutual funds. The evidence documents that while average return remains constant as the number of funds included in the FoF increases, risk is decreasing leading to improved generalised Sharpe ratios. At the same time, skewness and kurtosis coefficients present small deterioration. The investments strategy employed for the construction of a FoF plays its role: the choice of funds having good past performance results to FoF presenting properties that outperform not only the simple naive strategy, but also the composite index of Athens Exchange. Finally, the benefits of a FoF are maximised with the inclusion of only a small number of funds.